What Does it Mean to be a Montrealer? Multiculturalism, Cosmopolitanism and Exclusion Identity from the Perspective of Montreal's Ethnocultural and Linguistic Minorities - Catalano, Andy (Université d'Ottawa / University of Ottawa, 2016)
This thesis explores the meaning of the Montreal identity from the perspective of Montreal's ethnocultural and linguistic minorities. Generally speaking, it is commonplace for authors in the academic literature on Montreal to describe the city and its identity in terms of its multicultural and cosmopolitan sensibilities. While this forms part of what it means to be a Montrealer, this is not the only significance that this project accounts for. In examining the opinion sections of the Montreal Gazette from the period of September 4th, 2012 to the period of April 7th, 2014 ̶ a period that coincides with the Parti québécois' eighteen months in power under the leadership of Pauline Marois ̶ this thesis reveals that the meaning of the Montreal identity is tied to both the aforementioned multicultural and cosmopolitan sensibilities, as well as a sentiment of exclusion rooted in an ethnic interpretation of the Québec nation. Accordingly, this research also shows how these aspects of Montrealness contribute to the building of a Montreal identity that is meant to be distinct and even opposed to Québec identity.
Keywords: Montreal Identity; Quebec Nationalism; Montréalité; Montreal Gazette; identité montréalaise; Anglophones; exclusion identity; Montrealness; Multiculturalism; Comopolitanism